Ameliorative role of misoprostol on hematological and biochemical parameters of male rats’ treated with ciprofloxacin - Orass Saad Khayoon (University of Thi-Qar Journal of agricultural research, 2021)
Ciprofloxacin (CPX) is one of the most frequently used fluoroquinolone drugs used in treatment of infections caused by gram negative microbes. The currant aim of this study to ensure the defense action of misoprostol (MP) against undesirable effect induced by ciprofloxacin. Thirty white male rats were divided into three equal groups (first group: control group, second group: Ciprofloxacin group, which given ciprofloxacin at a dose 100mg/kg/day orally for 14 days, and third group: ciprofloxacin and misoprostol group, which given combination of ciprofloxacin at a dose 100mg/kg/day orally and misoprostol at a dose 200µg/kg/day orally for 14 days. After 14 day of treated, the rats were scarified, blood taken for measured RBC count, HB concentration, platelet number. WBC count and liver enzymes (ALT, AST, ALP). The results indicated a significant decrease (p < 0.05) of RBC, Hb, platelets and WBC in male rats treated with CPX compared with control group, also liver enzymes were increased significantly (p < 0.05) in CPX group compared with control group, while co-administration of misoprostol with CPX administration produce improving effects on hematological parameters and liver enzymes when compared with first and second group.